Promoting Preventive Behaviors of Nosocomial Infections in Nurses: The Effect of an Educational program based on Health Belief Model - Ali Khani Jeihooni; Seyyed Hannan Kashfi; Mina Bahmandost; Pooyan Afzali Harsini (Universidad de Antioquia, 2018)
Objective. To determine the effect of educational program based on Health Belief Model (HBM) on promoting preventive behaviors of nosocomial infections in nurses. Methods. In this randomized controlled trial study, 120 nurses working in a hospital in Fasa City, Fars (Iran). Intervention group (n=60) received an educational program based on HBM while control group (n=60) did not received it. A questionnaire consisting of demographic information, HBM constructs (knowledge, perceived susceptibility, perceived severity, perceived benefits, perceived barriers, self-efficacy, performance and cues to action) was used to measure changes toward the prevention of nosocomial infections before, immediately after intervention and four months later (of the end of the intervention). Results. Immediately and four months after the intervention, the intervention group showed a significant increase in the knowledge, perceived susceptibility, perceived severity, perceived benefits, Self-efficacy, cues to action and performance compared to the control group. Conclusion. This study in nurses showed that the effectiveness of the Educational program based on HBM on promoting preventive behaviors of nosocomial infections. Hence, this model can act as a framework for designing and implementing educational interventions for the prevention of nosocomial infections.   How to cite this article: Jeihooni AK, Kashfi SH, Bahmandost M, Harsini PA. Promoting Preventive Behaviors of Nosocomial Infections in Nurses: The Effect of an Educational program based on Health Belief Model. Invest. Educ. Enferm. 2018; 36(2):e09.